Fermented cottonseed meal improves production performance, immune function and intestinal microecological environment of laying hens and its nutritional properties - Xu, Mingyang; Li, Jia; Wang, Wei; Gao, Tongguo; Zhang, Caixuan; Hao, Zhimin; Zhou, Cheng (Frontiers in Veterinary Science, 2025)
IntroductionGlobal population growth and consumption upgrades have led to an increase in demand for animal feed protein sources, which has prompted an urgent need to find economical alternative protein sources. In this study, the potential of partially replacing traditional protein source soybean meal (SBM) with fermented cottonseed meal (FCSM) in practical applications were evaluated.MethodsThe 180 24-week-old Hyland Brown laying hens were randomly divided into a control group (CON, fed SBM) and an experimental group (FCSM, fed FCSM). The effects of FCSM on the production performance, immune system, intestinal morphology and microbiota composition of laying hens were investigated. Furthermore, the enrichment of FCSM for characteristic nutrient metabolites and key pathways was further explored.ResultsThe feed-to-egg ratio and egg quality indexes (eggshell thickness, eggshell strength, albumen height and Haugh units) of laying hens in the FCSM group were significantly better than those of the CON group (p < 0.05). Additionally, splenic index, immunoglobulins (IgG, IgM and IgA) and albumin/globulin ratio were stable in the FCSM group. FCSM significantly increased the species richness of the gut flora as well as the beneficial bacteria such as Rikenellace_ae_RC9_gut_group and Romboutsia (p < 0.05). Non-targeted metabolomics analyses indicated that microbial solidstate fermentation technology increased the levels of nutrients in CSM, such as L-glutamine, ornithine, citrulline, and D-galactose.ConclusionFCSM promoted the absorption of nutrients and intestinal health in laying hens by regulating the intestinal flora, demonstrating superior efficacy over BSM in overall production performance, immune function, and intestinal morphology. These findings provides a theoretical basis for the resource reuse in CSM and the precise nutrition of laying hens.